Components of teacher leadership in the modern learning management - Kanphao, Nutdaya; Supandee, Terdsaak; Sukserm, Pennapa (Journal of Green Learning, 2024)
This research aims to investigate the components of teacher leadership in modern learning management. The instruments used in the study include in-depth interviews, semi-structured interviews, and a researcher-made questionnaire for data collection. Content analysis was used to analyze the data. The research findings revealed 5 components of teacher leadership in learning management: 1) Technological literacy, which includes knowledge, skills, and attitudes toward basic technology and the promotion and development of technology; 2) Teamwork, which involves setting clear, shared goals, defining roles, and assigning tasks so that team leadership is actively involved; 3) Enhancing research literacy, which refers to knowledge, skills, and attitudes toward research; 4 ) Creative learning management, which involves designing learning through different methods to encourage and support learners to be innovative and share knowledge with each other, as well as assessing learners to reflect on their thinking and improve through different methods; and 5) Active leadership in learning management, which involves practical exercises, building learning networks and understanding assessment methods for learning.